The Eigenfunctions and Exact Solutions of Discrete mKdV Hierarchy with Self-Consistent Sources via the Inverse Scattering Transform (Advances in Applied Mathematics and Mechanics, 2018)
Another form of the discrete mKdV hierarchy with self-consistent sources isgiven in the paper. The self-consistent sources are presented only by the eigenfunctionscorresponding to the reduction of the Ablowitz-Ladik spectral problem. The exactsoliton solutions are also derived by the inverse scattering transform.